New Insights into Pathogenesis and Treatment of ANCA-Associated Vasculitis: Autoantibodies and Beyond - Marino Paroli; Chiara Gioia; Daniele Accapezzato (Antibodies, 2023)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis is a group of rare systemic diseases affecting small-caliber vessels. The damage caused by AAV mainly involves the lung and kidneys. AAV includes three different types: granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic granulomatosis with polyangiitis (EGPA). Although the different phenotypic forms of AAV share common features, recent studies have shown that there are significant differences in terms of pathogenetic mechanisms involving both the adaptive and innate immune systems. Advances in our understanding of pathogenesis have enabled the development of immuno-targeted therapies. This review illustrates the characteristics of the various forms of AAV and the new therapies available for this disease that can have lethal consequences if left untreated.